Analysis Of Changes In Seismic Rate (Seismic Rate Change) Based On Seismotektonic Spatial Distribution Of Bengkulu Area - Fadhil Ramadhani; Syafriani; Hamdi; Letmi Dwiridal (Journal of Experimental and Applied Physics, 2023)
Bengkulu Province has a high level of seismicity with significant earthquakes preceded by the phenomenon of decreased seismic activity (seismic quiescence) which can be seen through observing changes in seismic rate in an area based on the spatial distribution of z values. This study uses data from the USGS website for the period 1925-2021 to study seismic rates changes based on the spatial distribution of z values. In this study there are seven research focus zones, five major earthquake zones 1934 (7.0 SR), 1943 (7.0 SR), 2000 (7.0 SR), 2001 (7.0 SR), 2007 (7.7 SR), as well as two seismic activity zones with coordinates -5.6° to -4° south latitude and 101.6° to 103.4° east longitude and a seismic gap zone with coordinates –4.2° to -2.5° South latitude and 102.6° to 104.5° East longitude. The observation result show that before the earthquake occurred in the period 1925-2021, Before the earthquake, there had been a seismic quiescence phenomena. Four years before 2021, the seismic quiescence phenomena occurs in high seismic activity zones., while the seismic gap area occurs seven years before 2021. Overall, the seismic activity analysis result in Bengkulu province area shows an increase and decrease in seismic activity simultaneously in several different areas. This should be suspected of being the beginning of a significant earthquake in the future.